Relationship between Self-Compassion and Uneasiness about the Professional Future among Dental Hygiene Students: A Cross-Sectional Study - Maya Izumi; Sumio Akifusa (Hindawi Limited, 2023)
Purpose. To examine the self-compassion of dental hygiene students in Japan and the correlation between their self-compassion and uneasiness about their professional future. Methods. This study was conducted from May to September 2021. Students were invited from three colleges and one university in Fukuoka Prefecture to take the survey. Participants provided information regarding demographic variables (e.g., gender and year of study) and answered six questions regarding feeling uneasy about one's future, matters of learning, and what might happen after graduation. Self-compassion was assessed using the Japanese short version of the self-compassion scale (SCS), with the positive- and negative-SCS subdomains. Resilience was measured using the bidimensional resilience scale with the subdomains of innate and acquired resilience. For the statistical analysis, participants were divided into the "yes" group, where members felt uneasy and the "no" group, where members did not feel uneasy. Results. Data were obtained from 464 participants (response rate: 96.3%). The scores of total-, positive-, and negative-SCS were 36 (12-56), 18 (6-29), and 19 (6-30), respectively; 55.2% of students felt uneasy about their professional future. There was a statistically significant difference in scores for positive- and negative-SCS and innate resilience between the "yes" and "no" groups. Binomial logistic regression analysis revealed that when negative-SCS increased by one point, the risk of feeling uneasy about one's professional future was 1.12 times higher (95% confidence interval: 1.07-1.17) after adjusting for resilience and the answers to the remaining five questions. Conclusion. Our findings suggest that the negative factor of self-compassion is related to increasing the risk of feeling uneasy about one's professional future as a dental hygienist.